Trends in data replication strategies: a survey. Issue 2 (4th March 2019) - Souravlas, Stavros; Sifaleras, Angelo
ABSTRACT: Data Grids allow many organisations and individuals to share their data across long-distance areas. Nowadays, a huge amount of data is produced in all scientific fields and to enhance collaboration and data sharing, it is necessary to make this data available to as many nodes of the grid as possible. Data replication is the technique used to provide this availability. Moreover, it improves access time and reduces the bandwidth used. Recently, data replication has received considerable attention and several new algorithms have been developed. This article provides an overview of the state-of-the-art techniques of data replication. We identify the advantages and disadvantages of these strategies and discuss about their performance. Graphical Abstract: